Metode Karyawisata dalam Meningkatkan Kemampuan Menulis Karangan Deskripsi - Mimi Rosadi; Novita Friska Surbakti (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
The application of the field trip method aims as an alternative means for teachers to help students' interest in improving the ability to write essays that were previously a barrier to students in developing writing skills for each student. The field trip method also functions as an activity to eliminate the boredom of each student in learning, which teaches students to provide knowledge outside the classroom.